IMPLEMENTATION OF THE STORY METHOD WITH HELPING PICTURE MEDIA TO IMPROVE SPEAKING ABILITY AND ABILITY TO REMEMBER (Study at Kindergarten PGRI Kasih Ibu, South Bengkulu) - Yunita Apriyani; Bambang Sahono (UNIB Press, 2018)
The purpose of this study was to describe the application of the method of assisting with media images in increasing the ability to speak and remember early childhood in kindergarten PGRI Kasih Ibu, South Bengkulu Regency. The research design is collaborative CAR which means researchers or teachers together to learn to improve the quality or learning outcomes. Subjects in this study were children of Group B TK PGRI Kasih Ibu, South Bengkulu Regency, totaling 15 people. Data collection techniques use teacher observation sheets and child observation sheets (observation of speaking ability and recall ability). Data analysis uses the mean test and t test. The results showed that the method of storytelling assisted with image media could improve the ability to speak and remember early childhood in kindergarten PGRI Kasih, South Bengkulu Regency